2015
DOI: 10.5152/eajm.2014.55
|View full text |Cite
|
Sign up to set email alerts
|

The Success of Surgery in the First 24 Hours in Patients with Esophageal Perforation

Abstract: Objective: Esophageal perforation (EP) is a critical and potentially life-threatening condition with considerable rates of morbidity and mortality. Despite many advances in thoracic surgery, the management of patients with EP is still controversial. Materials and Methods:We retrospectively reviewed 34 patients treated for EP, 62% male, mean age 53.9 years. Sixty-two percent of the EPs were iatrogenic. Spontaneous and traumatic EP rates were 26% and 6%, respectively. Three patients had EP in the cervical esopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…TOM is the most crucial factor that influences the outcome of EP [15,16]. In our study, patients with late TOM had significantly higher rates of ICU admission, organ support need, reintervention, mean hospital stay, and morbidity.…”
Section: Discussionsupporting
confidence: 48%
“…TOM is the most crucial factor that influences the outcome of EP [15,16]. In our study, patients with late TOM had significantly higher rates of ICU admission, organ support need, reintervention, mean hospital stay, and morbidity.…”
Section: Discussionsupporting
confidence: 48%
“…Regardless of the etiology, severe esophageal perforation is a surgical emergency since patients can initially appear stable, but then decompensate quickly. [97][98][99][100] Decompensation usually results from esophageal and gastric contents leaking into the mediastinum with resultant necrotizing inflammation, sepsis, and ultimately multiorgan failure and death. 101,102 The Esophagus and Regenerative Medicine…”
Section: Esophageal Injurymentioning
confidence: 99%
“…Although there is no consensus on optimal management strategy, it is well established that prompt diagnosis and treatment within 24 hours of the perforation is associated with improved outcomes (1,(3)(4)(5)(6)(7)(8). In a metanalysis of 75 studies, Biancari et al (8) found a pooled mortality of 11.9%, however patients treated within 24 hours had a mortality of 7.4%, whilst those treated after 24 hours had a mortality of 20.3% (risk ratio 2.279, 95% CI, 1.632-3.182).…”
Section: Introductionmentioning
confidence: 99%